Deskripsi Kemampuan Berikir Kritis Matematis dan Kemandirian Belajar Siswa Ditinjau dari Gaya Belajar - Cici Mursari (Department of Mathematics Education, Universitas Muhammadiyah Purwokerto, Indonesia, 2019)
The study aimed to describe the mathematical critical thinking skills and learner autonomy of students at SMP Negeri 1 Baturraden viewed from learning style. This study was descriptive qualitative. The subjects of the study were students of grade VII G. The selection of the sample was done through purposive sampling technique obtaining 3 students of visual learning style, 3 students of auditory learning style and 3 students of kinesthetic learning style. Techniques to collect the data were questionnaire, test, and interview. Data analyses were data reduction, data presentation, and drawing conclusions. The validity test of the data was triangulation test of triangulation techniques. The findings obtained that students with visual learning styles mastered the indicators of analytical skills, synthesizing skills, problem solving skills as well as the skills of evaluating and assessing, meanwhile the learner autonomy mastered indicators of learning strategies, planning, evaluating, assignments/exercises, various learning resources and students workbook. Students with auditory learning styles grasped indicators of analytical skills, problem solving skills, as well as evaluating and assessing skills while for learner autonomy understood indicators of learning strategies, planning, evaluating, various learning resources and students workbook. While kinesthetic learning style students grasped the indicators of synthesizing and evaluating skills while for learner autonomy mastered the indicators of using learning strategies and using various learning resources.